Perceptions on farming as a profession: teenagers under the spotlight in Kwakyekrom in the Nsawam-Adoagyiri Municipality, Ghana - Osei, Enock; Keku, Emmanuel; Aluah, Daniel; Okoro, John Peter (Scientific Electronic Archives, 2022)
Food demand will continue to be on the increase due to rapid urbanization and population growth, amongst others. Thus, building and strengthening the capacities of human resources, and creating the avenue for young people to develop a passion for agriculture and its related endeavors is expedient. The study was to find out young people’s views and thoughts on farming and their willingness to take it up as a profession someday. A total of fifty-five (55) teenagers; 25 and 30 males and females, respectively were interviewed. With a majority, that is 35 (63.64%) in their middle adolescence, 47 (85.45 %) of the participants were at the Junior High School level. Investigating the association between some significant study variables, it was realized that there was a weak correlation (r < 1) among variables. However, at p < .05, there was a significant relationship between variables such as ‘gender’ and ‘willingness to be a farmer’ (r=.386, p=.004), ‘gender’ and ‘enjoy going to farm’ (r=.357, p= .009), ‘age’ and ‘enjoy going to farm’ (r=.372, p= .007), ‘ever want to be a farmer’ and ‘enjoy going to farm’ (r=.686, p=.001). Although most (67.27 %) participants’ parents/guardians were farmers, only 9 (16 %) participants ever wanted to be farmers. In ranking the perception of teenagers, “it is boring” was 1st followed by “it is for retirees”. As we embrace a world of digital innovations, reflecting in curriculum development, positive perspectives of agriculture should be established among teenagers by incorporating agriculture classes in the educational curriculum.